Comparison of the Effects of Local Injection and Oral Intake of Diclofenac and Atorvastatin in Alveolar Bone Density Assessed with CT in Experimental Periodontitis in Rat - Masoumi, Sara; Carassquer, Carlos Parra; Setoudehmaram, Shahin; Moatari, Maryam; Tanideh, Nader (Journal of Dental School, 2019)
Objectives The first cause of tooth loss in developed countries is periodontitis. Chronic periodontitis is the most common form of periodontitis and it is characterized by loss of periodontal attachment, destruction of alveolar bone and eventual loss of teeth. Atorvastatin is a statin drug used for the treatment of high cholesterol. Statins can stop the inflammatory process by inhibiting the cholesterol pathway. Diclofenac is an NSAID with anti-inflammatory, anti-pyretic and analgesic effects. Its primary mechanism is through the inhibition of prostaglandins synthesis by the inhibition of the cyclooxygenase enzyme (COX). The purpose of this study is to compare the effects of local injected and oral intake of Diclofenac and atorvastatin on alveolar bone density measured in HUs with the use of a CT scan in a periodontitis-induced model in rats. Methods Thirty rats were randomly divided into 6 groups of 5 rats each. Ligatures were placed around the left second maxillary molar to induce periodontitis for 10 days. Administration of 12.5 mg/kg of oral atorvastatin (group 1), 0.25 mg/kg of injectable atorvastatin (group 2), 7.5mg/kg of oral Diclofenac (group 3), 6.25mg/kg of injectable Diclofenac (group 4), the oral solvent without medicine as oral control (groups 5), and the injectable solvent without medicine as injectable control (group 6). In each group, the right side of maxilla was considered as control group (without ligature and drug interaction). At day eleven, the rats were sacrificed and the maxillary bone was separated from the soft tissue and fixed in 4% formalin. The prepared samples were then radiologically evaluated to determine the bone density with CT in fixed exposure conditions. Results There was a statistically significant difference between the alveolar bone density of the oral atorvastatin group and the oral Diclofenac (P = 0.006). There was no statistical significant difference in alveolar bone density between the injectable atorvastatin and the injectable Diclofenac groups (P=0.228). Conclusion Both atorvastatin and Diclofenac have shown better results when assessing bone density in a periodontitis rat model as compared to controls. Additionally, Diclofenac has been shown to be more effective at both oral and injectable administrations as compared with atorvastatin in the prevention of loss of bone density in a rat model with periodontitis.